Corpos de partida - Bezerra, Miguel Firmeza (2012)
Nests, textures, amalgams. Sustaining means to a broken, trespassed body. Path of experimentation and composition to a formation state. Invention of a second digestive operatory between body and movement. For a garden of mobile affections that tone up life. For a mobile texture digesting an unnamed life. For an incorporation state instead of a body. Means to the exercise of a strength hearing; strength like what produces a difference. Hearing as a means to differentiation. Active hearing that embodies movement in the body and body in the movement. Body-movement hearing as surface of a formation state, as practice of body production and experimentation with movement. Experimentation of the body-movement alliance. Platforms for a fruitful innocence